2012
DOI: 10.1007/s00216-012-6037-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of budesonide metabolites in human urine after oral administration

Abstract: Budesonide (BUD) is a glucocorticoid widely used for the treatment of asthma, rhinitis, and inflammatory bowel disease. Its use in sport competitions is prohibited when administered by oral, intravenous, intramuscular, or rectal routes. However, topical preparations are not prohibited. Strategies to discriminate between legal and forbidden administrations have to be developed by doping control laboratories. For this reason, metabolism of BUD has been re-evaluated using liquid chromatography-tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 34 publications
(49 reference statements)
3
63
0
Order By: Relevance
“…S1). The base peak at m / z 171 and low abundance of peaks at m / z 121 and 147 of Δ 6 ‐PRED were in agreement with mass spectra of previously described 6,7‐dehydrometabolites of budesonide and of methylprednisolone …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S1). The base peak at m / z 171 and low abundance of peaks at m / z 121 and 147 of Δ 6 ‐PRED were in agreement with mass spectra of previously described 6,7‐dehydrometabolites of budesonide and of methylprednisolone …”
Section: Resultssupporting
confidence: 90%
“…(E)). NL of 30 Da was present in 20 β ‐dihydro‐prednisone and has been reported in other corticosteroids, but its origin is not clear. The NL of 26 Da corresponds to a loss of acetylene .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As a consequence, great research activity has been developed to find strategies to distinguish allowed from forbidden administration for some compounds of the group. [11][12][13][14][15][16][17][18][19][20][21] For triamcinolone acetonide (TA), a drug related to THA, a previous study showed that a reporting level of 30 ng/mL was not able to detect forbidden IM administration. The use of a reporting level of 5 ng/mL was suggested to detect IM use as well as to distinguish IM from topical and intranasal administrations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out after the administration of different glucocorticoids (not only prednisone/prednisolone, but also methylprednisolone, budesonide, betamethasone and triamcinolone acetonide) have already shown that the reporting level of 30 ng/mL might not always be adequate for all glucocorticoids, especially in the case the parent compound is the only targeted analyte detected. [15][16][17][18][19][20][21][22] The goal of this study was focused on the definition of the excretion profile of both prednisone and prednisolone after the intake, via different routes, of therapeutic doses of some pharmaceutical formulations containing either prednisone or prednisolone, in order to select the most appropriate marker(s) of abuse, i.e., target(s) compound(s) excreted in urine in a concentration greater than 30 ng/mL for at least 24 h from the intake of the drug only in the case of systemic administration, and not produced in situ from natural steroids (i.e., cortisol and cortisone) by specific microorganisms.…”
mentioning
confidence: 99%